Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbantuan Mind Map Terhadap Keterampilan Pemecahan Masalah Peserta Didik Kelas XI SMA pada Materi Sistem Reproduksi - Putri Aulia; Fitri Arsih; Rahmawati Darussyamsu; Ria Anggriyani (Departement of Mathematics Education, 2023)
The application of learning models that haven’t been able to develop problem solving skills and the lack of preparation of students in learning causes low problem solving skills of students. This study aims to determine the effect of PBL learning model assisted by mind map on problem solving skills of class XI high school students on reproductive system material. This research used quasi experiment method with pretest-posttest control group design. The population in this study were students of SMAN 2 Pasaman in the 2022/2023 school year with a research sample of XI MIPA 1 class as the experimental class and XI MIPA 2 as the control class. Samples were taken using random sampling technique. Essay question were used as an assessment instrument. The results showed that the average pretest score in the experimental class was 46.74 and the control class was 38.04. The average posttest score in the experimental class was 77.48 and the control class was 67.68. The paired sample t-test test obtained the sig value. <0.05 which is 0.000, so it can be concluded that the PBL learning model assisted by mind map affects the problem solving skills of high school class XI students on reproductive system material.